Nuclease sensitivity of active chromatin. - Gazit, B (1980)
The active regions of chicken erythrocyte nuclei were labeled using the standard DNase I directed nick translation reaction. These nuclei were then used to study the characteristics and, in particular, the nuclease sensitivity of active genes. Although DNase I specifically attacks active genes, micrococcal nuclease solubilizes these regions to about the same degree as the total DNA. On the other hand micrococcal nuclease does selectively cut the internucleosomal regions of active genes resulting in the appearance of mononucleosomal fraction which is enriched in active gene DNA. A small percentage of the active chromatin is also released from the nucleus by low speed centrifugation following micrococcal nuclease treatment. The factors which make active genes sensitive to DNase I were shown to reside on individual nucleosomes from these regions. This was established by showing that isolated active mononucleosomes were preferentially sensitive to DNase I digestion. Although the high mobility group proteins are essential for the maintenance of DNase I sensitivity in active regions, these proteins are not necessary for the formation of the conformation which makes these genes preferentially accessible to micrococcal nuclease. The techniques employed in this paper enable one to study the chromatin structure of the entire population of actively expressed genes. Previous studies have elucidated the structure of a few special highly prevalent genes such as ovalbumin and hemoglobin. The results of this paper show that this special conformation is a general feature of all active genes irregardless of the extent of expression.